Investigation of the opioid system in absence seizures with positron emission tomography. Issue 12 (December 1993) - Bartenstein, P A; Duncan, J S; Prevett, M C; Cunningham, V J; Fish, D R; Jones, A K; Luthra, S K; Sawle, G V; Brooks, D J
Abstract : The neuroanatomical and pathophysiological basis of primary generalised absences is uncertain. Administration of endogenous opioids has been shown to result in absence-like seizures in animal models. Positron emission tomography scans were performed in eight patients with primary generalised epilepsy and eight control subjects. Regional cerebral blood flow was measured interictally with C15O2, after which a 90 minute dynamic study with the opioid-receptor ligand 11C-diprenorphine was performed. Serial absences were precipitated by hyperventilation for 10 minutes, starting 30-40 minutes after injection of diprenorphine. Absences, with generalised spike-wave discharges on the EEG, occurred for between 10% and 51% of the provocation period. No individual (normal or patient) had any interictal focal abnormalities of cerebral blood flow. After provocation of serial absence seizures, there was increased diprenorphine elimination from the association cortex, but not from the thalamus, basal ganglia, or cerebellum, compared with control subjects and patients scanned without provocation of absences. It was possible to simulate the observed increased diprenorphine elimination following seizures in cerebral cortex using a two tissue compartment model, with an estimated 15-41% decrease in the specific tracer uptake rate constant (k3). These results suggest that endogenous opioids are released in the association cortex at the time of serial absences, lead to increased receptor occupancy, and may have an important role in the pathophysiology of generalised absences.